2007
DOI: 10.1111/j.1601-0825.2006.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastomas: a regional Latin‐American multicentric study

Abstract: In this study we found that UA was frequently misdiagnosed as SA; however, there are enough clinical and microscopic features that allow for an accurate differentiation between both types of ameloblastoma that should be recognized for surgical and prognostic purposes. In this study, SA was not found in patients younger than 20 years, UA had a constant myxoid stroma while mature connective tissue was more frequently associated with the solid type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
60
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 13 publications
21
60
6
3
Order By: Relevance
“…5,9,13,23,24 The most frequent clinical presentation was of the solid ameloblastoma (61%) and, histologically, of the follicular variant (33%). This is very similar to what was observed in the studies conducted by Ledesma-Montes et al, 7 Osterne et al, 13 Saghravanian et al 15 and Santos et al 5 However, Fregnani et al 24 observed that the most frequent histological variant was the plexiform, which was observed in 53% of the cases. In our study, the posterior mandibular area was the preferred location, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…5,9,13,23,24 The most frequent clinical presentation was of the solid ameloblastoma (61%) and, histologically, of the follicular variant (33%). This is very similar to what was observed in the studies conducted by Ledesma-Montes et al, 7 Osterne et al, 13 Saghravanian et al 15 and Santos et al 5 However, Fregnani et al 24 observed that the most frequent histological variant was the plexiform, which was observed in 53% of the cases. In our study, the posterior mandibular area was the preferred location, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 59%
“…23 In our study, the incidence of ameloblastoma was 23% in all diagnosed cases, and these data are similar to findings from other studies. 7,14,18,20 No gender-related preponderance was noted in our study, which was different from other studies in which the incidence in the female gender was higher. 5,9,13,23,24 The most frequent clinical presentation was of the solid ameloblastoma (61%) and, histologically, of the follicular variant (33%).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations